2019
DOI: 10.1002/pchj.294
|View full text |Cite
|
Sign up to set email alerts
|

The roles of spatial frequency in category‐level visual search of real‐world scenes

Abstract: Visual object recognition appears to be effortless and virtually instantaneous for humans. A number of previous investigations have suggested that visual perception follows a coarse‐to‐fine processing sequence in which low‐spatial‐frequency (LSF) information provides a coarse representation of an object for an initial guess and guides the fine processing of the object based on high‐spatial‐frequency (HSF) information. A category‐level visual search of real‐world scenes shares many aspects of processing mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Evidence from behavioral experiments and neuroscience studies suggests that face perception is hierarchical, and involves multiple brain circuits (Bruce & Young, 1986; Calder & Young, 2005; Haxby, Hoffman, & Gobbini, 2000; Kanwisher, McDermott, & Chun, 1997; Maurer, Le Grand, & Mondloch, 2002; Xu, Dayan, Lipkin, & Qian, 2008). Each circuit may be specialized to process specific aspects of facial characteristics, including spatial frequencies (SFs; Badcock, Whitworth, Badcock, & Lovegrove, 1990; DeValois, Albrecht, & Thorell, 1982; Goffaux, Gauthier, & Rossion, 2003; Goffaux & Rossion, 2006; Halit, de Haan, Schyns, & Johnson, 2006; Jeantet et al, 2019; Zhang & Li, 2019). For example, the amygdala, an important subcortical region for emotion perception, favors low spatial frequency (LSF) information (Said, Baron, & Todorov, 2009); while the fusiform face area, one of the core regions for face perception, receives visual inputs at various SFs (Gauthier, Curby, Skudlarski, & Epstein, 2005).…”
mentioning
confidence: 99%
“…Evidence from behavioral experiments and neuroscience studies suggests that face perception is hierarchical, and involves multiple brain circuits (Bruce & Young, 1986; Calder & Young, 2005; Haxby, Hoffman, & Gobbini, 2000; Kanwisher, McDermott, & Chun, 1997; Maurer, Le Grand, & Mondloch, 2002; Xu, Dayan, Lipkin, & Qian, 2008). Each circuit may be specialized to process specific aspects of facial characteristics, including spatial frequencies (SFs; Badcock, Whitworth, Badcock, & Lovegrove, 1990; DeValois, Albrecht, & Thorell, 1982; Goffaux, Gauthier, & Rossion, 2003; Goffaux & Rossion, 2006; Halit, de Haan, Schyns, & Johnson, 2006; Jeantet et al, 2019; Zhang & Li, 2019). For example, the amygdala, an important subcortical region for emotion perception, favors low spatial frequency (LSF) information (Said, Baron, & Todorov, 2009); while the fusiform face area, one of the core regions for face perception, receives visual inputs at various SFs (Gauthier, Curby, Skudlarski, & Epstein, 2005).…”
mentioning
confidence: 99%
“…Visual recognition of scenes is a fast, automatic, and reliable process (Oliva, 2005 ; Greene and Oliva, 2009 ; Lowe et al, 2018 ; Kaiser et al, 2019 ). Thorpe et al ( 1996 ) have reported that complex natural scenes can be categorized under 150 ms. To explain this phenomenon, theories of visual perception have suggested a mode of processing based on specific spatial frequencies that would convey different information about the appearance of a stimulus (Kauffmann et al, 2015 ; Zhang and Li, 2019 ; Aghajari et al, 2020 ). High spatial frequencies (HSFs) represent abrupt spatial changes in visual information such as edges and correspond to configuration information and fine detail.…”
Section: Environmental Contextmentioning
confidence: 99%